Computational Docking of L-arginine and its structural analogues to C-terminal domain of escherichia coli arginine repressor protein (ARGRC) - Kueh, R.; Rahman, N.A.; Merican, A.F. (2003)
The arginine repressor (ArgR) of Escherichia coli binds to six L-arginine molecules that act as its co-repressor in order to bind to DNA. The binding of L-arginine molecules as well as its structural analogues is compared by means of computational docking. A grid-based energy evaluation method combined with a Monte Carlo simulated annealing process was used in the automated docking. For all ligands, the docking procedure proposed more than one binding site in the C-terminal domain of ArgR (ArgRc). Interaction patterns of ArgRc with L-arginine were also observed for L-canavanine and L-citrulline. L-Lysine and L-homoarginine, on the other hand, were shown to bind poorly at the binding site.